Analysis of inventory management at Widi Putra Motor - Dewa Nyoman Wahyu Ariana; Ica Rika Candraningrat (Interdisciplinary Social Studies, 2025)
The aim of this study is to analyze and compare the total cost of inventory by implementing a better inventory management system compared to the traditional methods currently used. This study was a descriptive research with a quantitative approach that focused on the analysis of inventory management at Widi Putra Motor, especially related to the effectiveness of controlling spare parts inventory using the Economic Order Quantity (EOQ) method. The object of the research consisted of inventories in 2023 and 2024. The results show that the use of the EOQ method provides efficiency in inventory management, which in turn minimizes costs incurred and supports the increase in profits. The total inventory cost is compared between the method applied by the workshop that is currently used and the method used by the shop. This research is expected to provide benefits both theoretically, as well as an empirical contribution and reference for future research related to inventory management. The application of the economic order quantity method is recommended to determine the optimal order quantity in order to minimize total inventory costs.